The Influence of Carbon Performance, Stakeholder Pressure and ISO 14001 Certification on Carbon Emission Disclosure - Ardhia Putri, Andi Vieska; Yuliandhari, Willy Sri (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study aimed to determine the effect of carbon performance, stakeholder pressure, and ISO 14001 certification on carbon emission disclosure. In Indonesia, the practice of disclosing carbon emissions is still limited. Based on the sample selection criteria, researchers analyzed ten companies from the energy sector listed on the Indonesia Stock Exchange for the period 2018-2022. The analysis method used is panel data regression analysis. The results of this study indicate that carbon performance and stakeholder pressure do not influence the disclosure of carbon emissions. At the same time, ISO 14001 certification has a significant positive effect on the disclosure of carbon emissions.